Inhibition of TRPC6 channels ameliorates renal fibrosis and contributes to renal protection by soluble klotho - Wu, Yueh-Lin (2017)
Fil: Wu, Yueh-Lin. University of Texas. Southwestern Medical Center. Department of Medicine. Division of Nephrology; Estados Unidos